Solvent- and Catalyst-Free One-Pot Green Bound-Type Fused Bis-Heterocycles Synthesis via Groebke–Blackburn–Bienaymé Reaction/SNAr/Ring-Chain Azido-Tautomerization Strategy - Gámez-Montaño, Rocio (2018)
A new, efficient, green, endogenous water-triggered, solvent- and catalyst-free ultrasound-assisted one-pot Groebke−Blackburn−Bienaymé reaction/SNAr/ring-chain azido-tautomerization strategy to synthesize bound-type fused bisheterocycles imidazo or benzo[d]imidazo[2,1-b]thiazoles and 1,5-disubstituted tetrazole (1,5-DsT) containing quinoline moiety is described, which allows synthesis of two types of fused heterocycles in one step under mild green conditions. Antibacterial and antiamebic activities of selected newly synthesized compounds were carried out against three bacterial species: Gram-positive bacterium Staphylococcus aureus ATCC 6538 and Gram-negative bacteria Pseudomonas aeruginosa ATCC 13384 and Escherichia coli O55 and against one amebic species: Entamoeba histolytica.